Unveiling the Symbolic: Literature and Cinema in John Patrick Shanley’s Dramaturgy (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2020)
John Patrick Shanley’s play Doubt - a Parable (2005) revisits the world he knew as a child, which is the Bronx of the 1960’s. The story centers upon a Catholic Irish-Italian school community, and the plot relates to a doubt - that grows into belief, and ends up as certainty - on the part of Sister Aloysius, the principal of the school, who is persuaded that Father Flynn, the vicar, has been harassing the only Black student in the school. In this paper, I examine the strategies used by Shanley to keep the possibility of interpretation open as he translates his own work into different media, on the page, on the stage and on the screen.